MANAJEMEN DAKWAH DALAM PERSPEKTIF EKONOMI: ANALISIS PEMINTAAN, PENAWARAN, DAN KESEIMBANGAN PASAR - Dewi Ratnawati; Ngatiyah; Annisa; Meity Suryandari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This article discusses the basic concepts of economics, particularly demand, supply, and market equilibrium, in the context of da'wah management. The influence of these economic variables on the effectiveness of da'wah activities is elaborated in detail, with the aim of providing a more comprehensive managerial perspective for da'wah practitioners. This study employs descriptive analysis and documentation methods with references from relevant economic books and journals. The results show that an understanding of basic economic concepts can assist in the more effective management of da'wah resources, as well as in maximizing the impact of da'wah activities themselves.. Keywords: Da’wah management, demand, supply, market equilibrium